The Analysis of Politeness Strategies in The Theatre of a Raisin in The Sun by Lorraine Hansberry - Sari, Agung Ayu Dyah Permata (Jurnal Penelitian Mahasiswa Indonesia, 2023)
In communicating, one needs to pay attention to people's faces to prevent being offended from the other person and more concerned with their feelings. Therefore, one needs to use a politeness strategy. Therefore, the purpose of this study is to describe the types and functions of politeness strategies in the theater of A Raisin in the Sun by Lorraine Hansberry. The method of this research is discourse analysis and uses the theory of politeness strategies proposed by Brown and Levinson. The results of this study are that there are several uses of politeness strategy, those are: (1) bald on record strategy used twice, the strategy of positive politeness once, the strategy of negative politeness twice, and the strategy of off record twice. Therefore, this strategy is used to maintain relationships with people who are known or not.